Designing Disability Insurance Reforms: Tightening Eligibility Rules or Reducing Benefits? - Andreas Haller; Stefan Staubli; Josef Zweimüller (Institute of Labor Economics (IZA), 2020)
We study the welfare effects of disability insurance (DI) and derive social-optimality conditions for the two main DI policy parameters: (i) DI eligibility rules and (ii) DI benefits. Causal evidence from two DI reforms in Austria generate fiscal multipliers (total over mechanical cost reductions) of 2.0-2.5 for stricter DI eligibility rules and of 1.3-1.4 for lower DI benefits. Stricter DI eligibility rules generate lower income losses (earnings + transfers), particularly at the lower end of the income distribution. Hence, to roll back the Austrian DI program, policy makers should implement tighter DI eligibility rules rather than lower DI benefits. An application of our framework to the DI system of the U.S. suggests that DI eligibility rules are too strict and DI benefits are too low.
Keywords: H53; H55; J14; J21; J65; 330; disability insurance; screening; benefits; policy reform